ANALISIS NILAI KEJUJURAN TOKOH “NUSSA” DALAM ANIMASI NUSSA DAN RARA AYU - Ayu Nuriyah Syibly; Taopik Rahman; Aini Loita (LPPM Universitas Cipta Mandiri, 2024)
This study aims to analyze the value of honesty in Nussa's characters in animations of Nussa and Rara.The type of research used is a qualitative approach with methods of content analysis. (content analylis).The results of research are known that Nussa and Rara's animations greatly give character values, oneof which is the value of honesty. Nussa's character has an honest personality, this is shown in thedialogue episode